(untitled) (International Journal of Engineering and Computer Science, 2015)
In the present investigation experimental work will be carrying out to estimate the performance, combustion and emission characteristics of a single cylinder, four stroke variable compression ratio multi fuel engine fuelled with honge oil blended with standard diesel. Tests has been conducted using the biodiesel blends of , 20%, 40% and biodiesel with standard diesel, with compression ratio 16:1-18:1 and an engine speed of 1500 rpm at different loading conditions. Present paper deals with effect of variation in compression ratio on engine performance and emission. Paper deals with effects on engine fueled with diesel, blend of diesel with biodiesel with a view to provide a platform for comparison of the parameter on various fuels. The performance parameters includes brake thermal efficiency (BTE), specific fuel consumption (SFC), brake power (BP), indicated mean effective pressure (IMEP), mechanical efficiency and exhaust gas temperature. The exhaust gas emission is found to contain carbon monoxide (CO), hydrocarbon (HC), nitrogen oxides (NOx) and carbon dioxide (CO2).